ADABU THALIB (ADAB SEORANG PELAJAR): ETIKA SEORANG PENUNTUT ILU - Bani Rif'ai, Deden; Fateh Al Muhibbin; Wahyu Al Karim Uszajalli; Muhammad Jundi Abdullah Robbaniy; Muhammad Akmansyah (Jurnal Pendidikan Bahasa Arab L-DHAD, 2024)
This abstract discusses the concept of adab in seeking knowledge, focusing on the term "Adabu Talib" which refers to the ethics and behavior that a seeker of knowledge should have. This research uses a qualitative approach with literature analysis from classical sources, including the book Hilyah Talib al-'Ilmi by Bakr bin Abdullah Abu Zaid. The results of the study show that the manners of a talib include sincere intentions for Allah, respect for teachers, and maintaining positive social interactions. In addition, Talib is also expected to have qualities such as patience, perseverance, and fear of Allah in the learning process. The emphasis on this adab aims to create a conducive and useful learning environment, both in this world and the hereafter. By understanding and applying manners in the search for knowledge, it is hoped that a talib can achieve higher educational goals and get the pleasure of Allah SWT. This research emphasizes that adab is a fundamental aspect in the search for sustainable knowledge. Keywords: ethics, behavior, seekers of knowledge.